Producing. - Anderson, Mark Lynn (Behind the Silver Screen Ser., 2016)
Producing is the first book to provide a comprehensive overview of the myriad roles that producers have played in Hollywood, from the dawn of the twentieth century to the present day. It introduces readers to the colorful figures who helped to define and reimagine the producer's role, including inventors like Thomas Edison, entrepreneurs like Walt Disney, and mavericks like Roger Corman. Along the way, we get an illuminating picture of the creative, managerial, and financial decisions that producers make.